Enhancing farm income resilience through climate smart agriculture in drought-prone regions of India - Samuel, Josily; Rama Rao, C. A.; Pushpanjali,; Anshida Beevi, C. N.; Raju, B. M. K.; Amarender Reddy, A.; Nagarjuna Kumar, R.; Reddy, A. Gopala Krishna; Singh, V. K.; Prabhakar, M.; Siva, G. Samba; Teggelli, Raju G. (Frontiers in Water, 2024)
The variability in climate affects the agricultural production especially in drylands. It is necessary to understand and quantify the impacts of resilient technologies as well as effects of extreme events. Keeping these in view, the primary data on household characteristics and the farm income was collected from a sample of 60 farmers each from National Innovations in Climate Resilient Agriculture (NICRA) program adopted village and a comparable control village in the district. The sample was also post classified into small, medium and large farmer to bring out the economic impact across land classes. The impact was estimated following the difference-in-differences (DiD) model as the data allows us to use effectively the data across time and regions. The results show us that the average income of a farm household in the NICRA village is more than 40 percent than non-adopted village and during a drought situation the farmers under NICRA intervention where better off by 19.5 percent. The income from crops and livestock production in adopted village was significantly higher than the control village. The DiD model output showed the farm income of adopted village was 40 percent higher showing that better climate smart interventions improved the farm incomes. The estimate showed that the treated farm household had higher income of Rs. 54,717 than the control during a drought year. Better knowledge and quantification of impact of technology adoption on farm income specially during drought will help to effectively design technological and policy interventions for better drought management in drylands.